Tuberous Sclerosis: a Review of Literature and Own Clinical Observation - Ye.V. Bordуugova; N.N. Konopko; D.S. Кhapchenkova; O.S. Kartashova (Zaslavsky O.Yu., 2013)
This article provides information on the origins, prevalence and clinical manifestations of tuberous sclerosis in children. The own clinical observation of a child with severe clinical course of this disease, caused by the early onset of neurological symptoms, multiple rhabdomyomas and skin manifestations.